The challenge to care in a Premier League Football Club - Cronin, C.; Knowles, Z. R.; Enright, K. (Sports Coaching Review, 2020)
Elite men`s football in the UK has been portrayed as a harsh and `uncaring` micro-political environment. Paradoxically, care has been identified as an essential aspect of coaching pedagogy. Thus, this study drew upon the experience of a case-study strength and conditioning coach to explore caring in a Premier League Football Club. A naturally occurring reflective diary served as a primary data source. Findings revealed that the coach "cared for" an athlete through a "rules based" approach, which thus far has not been described within coaching research. The narrative also suggested that care was constrained by the competitive context which requires coaches to "care about" results, and individuals around the club, e.g. themselves, staff and supporters. This study should prompt significant consideration by coaches who might examine how care is influenced by contextual factors, whilst simultaneously providing novel insights for coaching researchers who may further consider "rule based" approaches to care.